2018
DOI: 10.1158/1538-7445.sabcs17-p3-11-03
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P3-11-03: The impact of dose delays and reductions on toxicity and progression free survival (PFS) in patients receiving palbociclib

Abstract: Background: Despite the high rates of neutropenia observed in the PALOMA studies, the incidence of neutropenic fevers remained low. The safety analysis from the PALOMA-3 trial showed no difference in PFS among pts who had dose reductions or delays secondary to neutropenia. We conducted a retrospective study to analyze the impact of dose delays and reductions on toxicity and progression free survival (PFS) in pts receiving palbociclib as standard of care. Methods: Pts with metastatic ER positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
3
1
Order By: Relevance
“…We found that dose reduction was significantly associated with worse PFS. This is in contrast to what has been observed in randomized trials [ 35 , 36 , 37 , 38 ] and some other retrospective studies [ 39 , 40 ]. Upfront dose reduction and subsequent dose reduction due to toxicity could reflect poor patient-related prognostic factors, such as less favourable performance status and comorbidities.…”
Section: Discussioncontrasting
confidence: 96%
“…We found that dose reduction was significantly associated with worse PFS. This is in contrast to what has been observed in randomized trials [ 35 , 36 , 37 , 38 ] and some other retrospective studies [ 39 , 40 ]. Upfront dose reduction and subsequent dose reduction due to toxicity could reflect poor patient-related prognostic factors, such as less favourable performance status and comorbidities.…”
Section: Discussioncontrasting
confidence: 96%
“…In our study, the efficacy of palbociclib treatment was not affected by dose reductions, most frequently due to neutropenia. Our results are fully consistent with those from a retrospective report from the MD Anderson Cancer Center, which investigated the impact of dose delays and reductions on PFS in 334 patients receiving palbociclib in real‐life setting (Clifton et al, ). In terms of safety, no new issues emerged in our patient population and no cumulative toxicity was reported.…”
Section: Discussionsupporting
confidence: 89%
“…As previously reported, this did not seem to affect treatment effectiveness. [14][15][16]36,43,44 The strength of the present experience is the prospective evaluation in a large cohort of unselected breast cancer patients of palbociclib plus ET combinations in a real-world setting with a long follow-up time. Our data also provide information concerning the prior treatment with fulvestrant and/or everolimus, confirming no detrimental effect of both the agents on palbociclib-treated patients.…”
Section: Discussionmentioning
confidence: 99%